Społeczeństwo wiedzy i organizacje wiedzy. O roli menedżerów w nowoczesnych procesach społecznych - Banaszak, Sławomir (Wydawnictwo Naukowe UAM, 2017)
Managers are very important part of modern organizations and societies. The paper is an attempt at showing managers as a factor of creating knowledge organizations. The author points at qualifictions and competences of managers as the main issue in this process. Problems of “knowledge production” and “knowledge processing” are revealed. The paper ends with the approach to the problems of economic efficiency of knowledge and its positive impact on organizations and societies
Knowledge Society and Knowledge Organizations. On the Role of Managers in Modern Social Processes
Keywords: knowledge society; knowledge organization; managers; competencies; knowledge management